INCAPACIDADE FÍSICA NA PESSOA COM HANSENÍASE E A ASSISTÊNCIA DAS EQUIPES DA ESTRATÉGIA SAÚDE DA FAMÍLIA EM MATO GROSSO DO SUL - Ana Paula Ribeiro Mijolaro Lagemann (2023)
Leprosy is a disease of great disabling power and still represents a serious public health problem in Brazil. Physical disabilities signal late diagnosis and precarious care. Our objective was to evaluate the frequency of physical disability in people with leprosy and the assistance provided by the Family Health Strategy (ESF) teams in Mato Grosso do Sul. A descriptive, quantitative research was carried out, using primary and secondary data from Mato Grosso do Sul, in the period from 2016 to 2020. Primary data were collected through a questionnaire with 34 questions, for doctors and nurses of the Health Units with ESF (US /ESF) and who reported cases of leprosy between 2018 to 2020 and to physiotherapists, who treated cases of leprosy in different health services. Eighty two professionals from 27 municipalities participated, 54 nurses, 19 physiotherapists and 9 physicians. Of this total, 60 (73.17%) work in US/ESF and 22 (26.83%) in other services. The 19 physiotherapists participate in the early diagnosis and assistance, fill out the assessment form of the Degree of Physical Disability (GIF) at diagnosis and at discharge and the simplified neurological assessment. In the US/ESF, only 45.00% reported carrying out GIF assessment and shortage of materials: dental floss, esthesiometer, glass tube, Snellen chart, in the other US the GIF is being performed (72.72%) despite the shortage of essential materials, except esthesiometer. Secondary data were collected from the Notifiable Diseases Information System (SINAN) on the DataSUS website, from new cases, residing in the state, notified between 2016 and 2020, cured and evaluated using Ministry of Health parameters. Among the 1,900 new cases, GIF at diagnosis was 81.89%, GIF2 in 12.85%, not evaluated or ignored, 18.10%, “regular” parameter. In the cure cohorts, GIF was 72.12%, GIF2 in 6.17%, not evaluated or ignored, 27.87%, “poor” parameter. GIF2 at diagnosis was high and at discharge it was compromised by the absence of the minimum necessary evaluation. The GIF2 at patient admission was high, signaling delay in diagnosis. The precariousness of the GIF evaluations demonstrates the fragility of care and compromised action planning at all levels of care. Patients, at diagnosis, present physical disability above the acceptable level and at discharge due to cure, they are underdiagnosed, showing low quality of care. This assistance must comply with established protocols, focused on early diagnosis, treatment, cure, assessment of physical disability at diagnosis, during treatment and at discharge, and rehabilitation for cases with installed physical disability. Our findings indicate the need to strengthen primary care and reference services in physiotherapy, with the availability of fundamental materials in assessments, in addition to theoretical and practical training/capacity building, for physiotherapists, addressing clinical management, physical assessment, sensitivity assessment, prevention and rehabilitation. Descriptors: Family Health; Leprosy; Modalities of Physiotherapy; Epidemiology